Cushing’s Syndrome: A Large Adenoma of Adrenal Gland - M Adi Soedarso; K Hery Nugroho; Erik Prabowo; Devia E Listiana; Danu Soesilowati; A Gunawan Santoso (Acta Medica Indonesiana)
A 20-year old  man was admitted for evaluation of Cushing’s syndrome. He presented with a history of headache, fatique, mood disorder, hypertension (Blood Pressure 170/120 mmHg), moon face, buffalo hump, striae rubrae.  Cortisol serum laboratory increased  33.53 µgr/dl (Normal range: 3.09 – 16.6µgr/dl). Abdominal CT Scan showed a right adrenal mass diameter 10.53 x 6.83 cm, with calcified and necrotized area. Levels of ACTH < 5 pg/ml (Normal range : 6 – 50 pg/ml), absence hypothalamus pituitary defect in brain MRI angiography lead the primary site on adrenal. Patient was given ketoconazole 600 mg daily to treat hypercortisolemia. The patient underwent laparoscopic right adrenalectomy. Preparation of hydrocortisone 100 mg during anesthesia-surgery to prevent occurrence of adrenal crisis. Patient position was LLD, 11mm trocar port with 0, 30 degree optic, 2 port 5mm was used for working element. Harmonic ultrasoundshear was used for dissection, hemoLock clip to control vascular. Right subcostal incision make to remove adrenal gland. EBL 1000 cc, close monitoring in ICU ward. Hydrocortison was continued 5 days after surgery. Ventilatory support removed in 2 day after surgery. On the fifth day condition stable without signs of adrenal crisis, and the patient sent to elective ward. The pathology report revealed a cushing adenoma of adrenal gland. On the fifth day after surgical intervention,  postoperative cortisol levels at 12 µgr/dl. On seventh day, surgical wound healing was well with minimum dose NSAID orally. Striae thining, ginecomastia, buffalo neck, moon face was reduced. The patient was regularly followed up at Endocrine division, Department of Internal medicine. Moon face have been eliminated, no striae and  good mood condition. Blood pressure was 130/ 70 mmHg (without antihypertensive drugs) and cortisol serum was 4.52 µgr/dL and independent from steroid medication. Multidisciplinary approach including endocrine treatment, prevention adrenal crisis and laparoscopic adrenalectomy procedure have good result for Cushing’s syndrome due to adenoma of adrenal gland.